Exophtalmie unilatérale révélateur d’une fistule carotido-caverneuse : A propos d’un cas au CHU-IOTA - M, SISSOKO; I, Conaré; D, Sissoko; S, Diarra; G, Saye; M, Coulibaly; N, Guirou (Jour Med Resh and Health Sci, 2023)
We report a particular observation in an 11-year-old boy with no notion of trauma in whom the parents noticed an asymmetry between the eyes since birth; According to them, this is a temporary situation. Given the persistence and the increase in the volume of his right eye, they decided to consult pediatrics who referred us for right palpebral malformation. CT angiography confirmed the diagnosis of a carotid-cavernous fistula, which is responsible for this symptomatology. The objective of this article is to shed light on this rare pathology, emphasizing the clinical and therapeutic particularities.